2007
DOI: 10.1200/jco.2007.10.7573
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Joint Symptoms in Postmenopausal Women Taking Aromatase Inhibitors for Early-Stage Breast Cancer

Abstract: Our study suggests that AI-related joint symptoms are more prevalent than what has been described previously in clinical trials. The success of AI therapy depends on patients' ability to adhere to treatment recommendations; therefore, additional studies of interventions that may alleviate these symptoms are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
330
7
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(371 citation statements)
references
References 34 publications
24
330
7
10
Order By: Relevance
“…The lowest incidence has been reported for exemestanetreated patients in the IES. However, other reports did not show differences in incidences of musculoskeletal symptoms between the three AIs (Crew et al 2007). These conflicting results are due to the variable definitions used in the several trials.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 77%
See 2 more Smart Citations
“…The lowest incidence has been reported for exemestanetreated patients in the IES. However, other reports did not show differences in incidences of musculoskeletal symptoms between the three AIs (Crew et al 2007). These conflicting results are due to the variable definitions used in the several trials.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 77%
“…Although the reported incidences of AI-induced musculoskeletal symptoms range from 5-36.0% in the large clinical trials (Howell et al 2005, Coombes et al 2007, Crew et al 2007, Gaillard & Stearns 2011, more than half of patients complain of these adverse events in the clinical setting (Presant et al 2007, Lintermans & Neven 2011. The lowest incidence has been reported for exemestanetreated patients in the IES.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 96%
See 1 more Smart Citation
“…One concern among experts was performing step exercise by patients at the risk of joint problems. Results of a study revealed that joint symptoms are very common in breast cancer patients taking aromatase inhibitors as 47% of them reported joint pain and 44% reported joint stiffness (8). Therefore, caution must be taken when prescribing step exercise, or any other kind of exercise affecting joints, for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Crew and colleagues have recently published results of a prospective cohort study in which 200 women initiating AIs completed a self-administered questionnaire concerning joint pain and stiffness [15]. Nearly half of the women reported one of the two symptoms; 47% reported joint pain and 44% joint stiffness.…”
mentioning
confidence: 99%